2021
DOI: 10.1080/17565529.2021.1930509
|View full text |Cite
|
Sign up to set email alerts
|

Puppeteering as a metaphor for unpacking power in participatory action research on climate change and health

Abstract: The health impacts of climate change are distributed inequitably, with marginalized communities typically facing the direst consequences. However, the concerns of the marginalized remain comparatively invisible in research, policy and practice. Participatory action research (PAR) has the potential to centre these concerns, but due to unequal power relations among research participants, the approaches often fall short of their emancipatory ideals. To unpack how power influences the dynamics of representation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that this methodological approach is well suited for conducting municipal climate adaptation research (e.g. Boezeman et al 2014;Campos et al 2016;Ruiz-Mallén 2020;Meriläinen et al 2021;Vizinho et al 2021). Inspired by these studies, a PAR network for the federal state of Baden-Wuerttemberg, in Germany, was initiated and established at Aalen University in 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that this methodological approach is well suited for conducting municipal climate adaptation research (e.g. Boezeman et al 2014;Campos et al 2016;Ruiz-Mallén 2020;Meriläinen et al 2021;Vizinho et al 2021). Inspired by these studies, a PAR network for the federal state of Baden-Wuerttemberg, in Germany, was initiated and established at Aalen University in 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the process, the research facilitators were conscious of the need to balance the goals of the research with those of FPAR as an empowering process. We remained conscious of the potential for PAR approaches to retain asymmetrical power relationships and that the young women researchers' and community's priorities may be contrary to the framings of the research and action agenda around climate change and education [24]. Critical researchers studying climate resilience in development contexts have highlighted the importance of agency and empowerment as drivers of transformation that can enable wider ranges of choices within these pathways towards high resilience, low risk, and high welfare outcomes [15,25].…”
Section: Conceptual Approach: Feminist Participatory Action Researchmentioning
confidence: 99%